The name for a well-known crop: Rumex kioviensis, a hybridogenous taxon derived from R. patientia × R. tianschanicus (Polygonaceae) - Rakhmetov, Dzhamal B.; Mosyakin, Andrii S.; Mosyakin, Sergei L. (Phytotaxa, 2024)
The new crops developed at the M.M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine in Kyiv from the initial artificial interspecific crosses Rumex patientia × R. tianschanicus are variously known in botanical and agricultural literature under the hybrid formula or informal names “Shchavnat”, “Hybrid Dock”, “Rumex K-1”, “Rumex OK-2”, or names of cultivars cv. ‘Kyivskyi Ultra’, cv. ‘Shpinat Uteusha’, cv. ‘Nastavnyk’, etc. A brief overview of the history of development of these cultivars is provided. These robust perennial plants are cultivated at present as spinach greens, fodder, and high-yield biomass producers for bioenergy applications in several European and other countries (Ukraine, the Czech Republic, Slovakia, Germany, Romania, etc.). Numerous agricultural, horticultural, and biotechnological publications about these new crops are now available, including various aspects of and data on their biochemistry, physiology, genetics, morphology, propagation, agrotechniques, biomass and biofuel production potential, nutritional value, etc. Also, these hybrid cultivars were reported in several regions of Central Europe as potentially invasive weeds escaped from cultivation. Considering the growing popularity of the Hybrid Dock as a green leaf vegetable, a biomass and biofuel producing crop (among other uses), and a potentially invasive alien, we think that a proper botanical name should be assigned to that taxon. Here it is described as a new hybridogenous species Rumex kioviensis Rakhmetov, A. Mosyakin & Mosyakin. Diagnostic characters distinguishing this new taxon from its parent taxa and other related species are indicated. Some remaining taxonomic and nomenclatural problems regarding Asian taxa related to R. patientia are briefly discussed.